2017
DOI: 10.2147/ov.s123292
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory response induced by Newcastle disease virus in tumor and normal cells

Abstract: Purpose: To investigate the specific role of immune responses induced by lentogenic Newcastle disease virus (NDV) for its antitumor effect. Materials and methods: NDV LaSota strain was used to infect the following human cells: non-small cell lung carcinoma (A549), glioblastoma (U87MG and T98G), mammary gland adenocarcinoma (MCF7 and MDA-MB-453), hepatocellular carcinoma (Huh7), transformed embryonic kidney cells (HEK293), primary monocytes, lung fibroblast (HF19), skin fibroblast (NB1RGB) and rat astroglia (RC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 40 publications
1
32
0
Order By: Relevance
“…Lytic strains are able to produce infectious progeny by disrupting the plasma membrane of infected cells, while non-lytic strains mainly stimulate immune responses. 73 An interesting observation to highlight is that both strain types have antitumor potential, 74 with a non-lytic strain being superior to a lytic strain in some instances. 75 Thus, the way tumor cells die, or in other words, the way OVs kill tumor cells, can make a significant difference in terms of OVT success, drawing into question the need for "lytic" outcomes with OVs.…”
Section: Ovt As Immunotherapymentioning
confidence: 99%
“…Lytic strains are able to produce infectious progeny by disrupting the plasma membrane of infected cells, while non-lytic strains mainly stimulate immune responses. 73 An interesting observation to highlight is that both strain types have antitumor potential, 74 with a non-lytic strain being superior to a lytic strain in some instances. 75 Thus, the way tumor cells die, or in other words, the way OVs kill tumor cells, can make a significant difference in terms of OVT success, drawing into question the need for "lytic" outcomes with OVs.…”
Section: Ovt As Immunotherapymentioning
confidence: 99%
“…NDV elicits both an innate and adaptive immune response in the TME by inducing IFN production and immune cell infiltration and maturation 7, 8, 9, 11, 12. In this study, local injection of NDV in HCC induced an immune response and infiltration of CD8 + T and NK cells in the TME.…”
Section: Discussionmentioning
confidence: 50%
“…NDV is a member of the Avulavirus genus of the Paramyxoviridae family. In both preclinical and clinical studies, NDV induced the production of type I IFNs and is an effective oncolytic agent with a good safety record 7, 8, 9. On one hand, NDV induces both extrinsic and intrinsic apoptosis of malignant cells, 10 and on the other hand, NDV infection elicits both innate and adaptive antiviral immunity, resulting in cross-activated antitumor immune responses 11, 12.…”
Section: Introductionmentioning
confidence: 99%
“…While NDV has been examined in the past as an oncolytic vector, only in recent years has it been tested in breast cancer. A recent study, assessing the pro-inflammatory response to NDV in a number of tumor lines, including breast cancer, found that NDV is a potent activator of type I and II interferon responses in addition to Interleukin 6 (IL-6) expression [ 89 ]. The authors of this study concluded that NDV has potential as an immunotherapeutic agent.…”
Section: Group V Virusesmentioning
confidence: 99%